Atividades psiquiátricas no campo dos transtornos devidos ao uso de substâncias psicoativas - Sonenreich, Carol; Kerr-Correa, Florence [UNESP]; Estevão, Giordano; De Moraes Altenfelder Silva Filho, Luis (My University, 2002)
There are a large number of institutions, proposals and publications in the field of disorders resulting from the use of psychoactive substances. There is no corresponding progress in results obtained in clinical treatments. Concepts and appropriate points of view are indispensable. The vision of the world drug addicts is not only determined by the biochemical effects of intoxication, but also by the experience they go through, by their own way of living. By accepting such postulate, we may conceptualize the problem, thus benefiting research studies and more efficient treatments. Preventing intoxication, upon the onset of dependence, depends on educational, social, legal and other measures, which can neither be studied nor practiced by medicine.
Psychiatric activities in the field of disorders resulting from the use of psychoactive substances
Keywords: Alcoholism; Psychiatry; Psychoactive substances; psychotropic agent; drug dependence; drug intoxication; health education; human; legal aspect; medical practice; preventive medicine; review; social aspect; treatment planning